Absence of SARS‐CoV‐2 infection in the semen of men recovering from COVID‐19 infection: An exploratory study and review of literature. (11th June 2021) - Sharma, Aditya Prakash; Sahoo, Swapnajeet; Goyal, Kapil; Chandna, Abhishek; Kirubanandhan, Sangeetha; Sharma, Vikrant; Grover, Sandeep; Singh, Mini P.; Bhalla, Ashish; Singh, Shrawan K.
Abstract: The effect of COVID‐19 on the male reproductive tract has been sparsely studied. This exploratory study was designed to determine the presence of SARS‐CoV‐2 in the semen of men recovering from COVID‐19. A systematic literature review was also performed as per PRISMA guidelines to gather perspective on this topic. The prospective study included men 21 years and older recovering from COVID‐19 with nasopharyngeal swab negative for SARS‐CoV‐2 or at least two weeks from the last COVID RT‐PCR positivity. After clinical evaluation, freshly ejaculated semen sample by masturbation was collected in a sterile container. Samples were processed for the detection of SARS‐CoV‐2 by RT‐PCR. Twenty‐one patients were contacted for the study, 11 of which consented to provide a semen sample. The mean age of the cohort was 29.72 ± 4.52 years. None of the patients gave a history of epididymo‐orchitis or sexual dysfunction at the time of assessment. None of the semen samples demonstrated SARS‐CoV‐2 on RT‐PCR. Median duration of semen sample collection from the COVID positivity was 44 days (Range 19–59 days). Detailed literature review revealed that SARS‐CoV‐2 is not found in patients recovering from COVID‐19 infection. We conclude that SARS‐CoV‐2 is not found in the semen of patients recovering from COVID‐19.